Análisis de la dinámica del IVA externo derivada de la ejecución del TLC con estados unidos en el periodo 2012-2016 (2018)
The current business model, supported by the neoliberal system of thought, which tends towards the deregulation and liberalization of markets and economies, whose policy orientations were enshrined in the Washington Consensus; assumes that the effects of the application of such measures are of general benefit to the economy, improving productive efficiency and economic development. Within the framework of the aforementioned guidelines, the country has directed its external commercial dynamics, through the signing of free trade agreements (FTA). In this sense, the research carried out was aimed at quantitatively and qualitatively analyzing the behavior of external VAT derived from imports, ex ante and ex post, of the signing of the FTA with the United States, Colombia's main trading partner.